Perbandingan Pandangan Hakikat Manusia antara Islam dan Pemikiran Barat: Perspektif Teologis dan Filsafat - Alifah Fauziyah; Afdan Hakim (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
The concept of human nature is a fundamental theme in theology and philosophy as it forms the basis for understanding the purpose of life, morality, freedom, and human responsibility. Islam and Western thought employ different conceptual frameworks in interpreting human nature, particularly in ontological, epistemological, and axiological aspects. This article aims to analyze and compare Islamic and Western perspectives on human nature through theological and philosophical approaches. The study adopts a qualitative method based on library research using comparative analysis of Islamic theological sources and classical as well as contemporary Western philosophical works. The findings indicate that Islam views human beings as creatures of God who possess integrated physical and spiritual dimensions, with freedom inseparable from moral responsibility and transcendental purpose. In contrast, Western thought presents diverse perspectives that tend to emphasize human rationality and autonomy, highlighting individual freedom and the immanent construction of meaning. These differing perspectives have significant implications for understanding freedom, morality, and life orientation. This comparative study underscores the importance of a balanced analytical approach to achieve a more comprehensive understanding of human nature and to foster constructive dialogue between Islamic and Western thought in contemporary intellectual discourse.